Green approach for the valorization of microalgae Tetradesmus obliquus - Gouveia, Luisa (2022)
The main goal of this study was to develop an efficient, green approach for the valorization of Tetradesmus obliquus biomass, with zero waste. This microalga was selected because it is widespread, resistant, easy for cultivation, and fast-growing. In the first step, supercritical carbon dioxide (ScCO2) extraction followed by rapid gas decompression was used for the extraction of biomass. The following step was to apply ultrasound-assisted (UA), microwave-assisted (MA), and subcritical water (SW) extraction on the ScCO2-treated biomass to determine the most efficient processing technology. SW demonstrated to be a superior technique over MW and UA with regard to extraction yield and antioxidant content. Moreover, the chemical and microbiological profiles of SW extracts were determined to evaluate their potential and safety. In addition, to create a procedure with zero waste, the solid waste after SW extraction (residue) was analyzed. The organic profile of extracts and residues contained compounds that belong to groups of aliphatic saturated hydrocarbons, aliphatic unsaturated hydrocarbons, alkylated hydrocarbons, ketones, phenols, and esters. Furthermore, these compounds can be applied in different industries including the pharmaceutical and cosmetic industries. Additionally, the content of metals in residues indicated that this material can be used as animal feed and in agriculture. Finally, a complete reduction of microorganisms present in the initial biomass was obtained for the extracts and residues, indicating their safety.